1988
DOI: 10.1139/x88-032
|View full text |Cite
|
Sign up to set email alerts
|

Tree life history strategies: the role of defenses

Abstract: Analysis of energy partitioning between defensive investments and growth in woody plants indicates that increasing a tree's life-span should require increased energy investment in protective measures such as thick bark and defensive chemicals. Increased investment in such defenses, however, logically must slow down the growth rate, thereby raising the mortality rate for juveniles in competition for height growth. Early reproduction should also reduce the growth rate. It is hypothesized that rapid growth can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
320
2
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(338 citation statements)
references
References 0 publications
13
320
2
3
Order By: Relevance
“…When lighting conditions improve, most seedlings significantly accelerate their growth. Some recent studies also revealed that trees with early slow growth lived longer than fast-growing trees (Loehle 1988, Johnson & Abrahms 2009). …”
Section: Discussionmentioning
confidence: 97%
“…When lighting conditions improve, most seedlings significantly accelerate their growth. Some recent studies also revealed that trees with early slow growth lived longer than fast-growing trees (Loehle 1988, Johnson & Abrahms 2009). …”
Section: Discussionmentioning
confidence: 97%
“…Low wood density species show, therefore, a faster height growth (Muller-Landau 2004;Poorter 2008;King et al 2005) and a low wood density is therefore especially advantageous for light-demanding species that need to monopolize gaps by growing rapidly in height and complete their life cycle before they are being overtopped by competing neighbouring plants. Wood density is emerging as a core functional trait (Chave et al 2009), not only because of its importance for tree stability and architecture (King et al 2006) but also because of its importance for defence against pathogens (Loehle 1988), stem hydraulics and cavitation resistance (Pratt et al 2007;Markesteijn et al 2011), and hence, photosynthetic carbon gain (Santiago et al 2004). The effect of wood density was largely maintained in the ANCOVA analysis, suggesting that wood density may contribute to architectural variation not only between families but also within families.…”
Section: Wood Densitymentioning
confidence: 99%
“…This variable is closely related to the resistance to wood to rupture and self-loading (van Gelder et al 2006;Chave et al 2009), and hence, to the production of stable horizontal branches, resistance to external forces, and mechanical stability. Wood density also plays a central role in the life history variation of tree species as low-density wood is cheap to construct, allowing for rapid growth in stem dimensions, whereas highdensity wood allows for a high survival rate and long lifespan (Loehle 1988;Poorter 2008;King et al 2006). Wood density may therefore be closely related to the shade tolerance of the species.…”
Section: Introductionmentioning
confidence: 99%
“…This paper singles out the plant's control over the turnover of organic matter and points towards a critical role for protective leaf traits (against the biotic or abiotic environment) that act against herbivores and allow long leaf lifespans (Coley, 1980 ;Chabot & Hicks, 1982 ;Southwood et al, 1986). Such ' defences ', which seem to have a strong genetic basis, occupy one side of a fundamental, interspecific trade-off against traits that confer the potential for fast plant growth (Coley et al, 1985 ;Coley, 1988 ;Loehle, 1988 ;Herms & Mattson, 1992 ;Poorter & Bergkotte, 1992 ;Chapin et al, 1993 ;Grime et al, 1997 ;Cornelissen et al, 1998), the latter itself a major determinant of ecosystem function (Grime, 1979). Another way of approaching the same trade-off (see the Discussion section) is to compare species in terms of emphasis on resource acquisition versus resource conservation (Lambers et al, 1998 ;Poorter & Garnier, 1999).…”
Section: mentioning
confidence: 99%